SHAPE OPTIMIZATION OF GLIDER WING GL-1 USING CFD ADJOINT SOLVER METHOD - Ahmad Maulana, Faridl
Adjoint method is one of computational fluid dynamic-based optimization tools for optimizing the aerodynamic shape of the body. The method is rarely used in aircraft because it still in development process. However, this research attempt to use adjoint method on optmizing GL-1 Glider which is the first national Glider of Indonesia. The purpose of this optimization is to increase the aerodynamics performance of GL-1 with optmizing its wings. Adjoint as an optimization method in this research have done with using Adjoint Solver modul provided by CFD software ANSYS Fluent. The decision to optimize the wing comes from previous CFD study that the biggest contribution of drag is from wing. The ideal target of optimmization is increasing L/D by the way reducing drag. But after a study of adjoint method on Fluent Adjoint Solver and investigation on the aspect and parameter of adjoint it was found that there is limitation in adjoint method to use fine mesh to calculate drag accurately. Therefore it is decided to optimize the shape with increasing lift as a target. This research report presents the result of study of adjoint method and its implementation on the wing of GL-1 Glider. Flight condition is as resulted from previous CFD study in the maximum range condition, with velocity of 25 m/s and angle of attack of aircraft is 0 degree by using incidence angle of 2 degree to the wing. Wing baseline has value of CL = 0.81 and CD = 0.0271. The optimized wing achieved the optimum result of CL = 1.02 and CD = 0.0362 by applying adjoint method.